A tale of two islands: evidence for impaired stress response and altered immune functions in an insular pit viper following ecological disturbance. Issue 1 (3rd May 2020) - Sandfoss, Mark R; Claunch, Natalie M; Stacy, Nicole I; Romagosa, Christina M; Lillywhite, Harvey B
Abstract : There is an increasing need for conservation tools that allow scientists and managers to assess the physiological and immune health of free-ranging animal populations. We evaluated several commonly used biomarkers to characterize the health of two insular snake populations with markedly different availability of food resources after ecological disturbance. Abstract: The frequency and intensity of ecological perturbations affecting wild animal populations is expected to increase in the future with animals facing numerous global threats. Seahorse Key is a continental island off mainland Florida that has historically been a major rookery for several species of waterbirds. As a result of an unknown disturbance, the entire rookery abandoned Seahorse Key in April 2015 and shifted nesting activities to nearby Snake Key, resulting in an influx of food resources in the form of fish carrion to resident Florida cottonmouth snakes ( Agkistrodon conanti ), while snakes on Seahorse Key experienced a drastic reduction in food resources. Our objective was to assess plasma corticosterone concentrations, corticosterone negative feedback using dexamethasone, blood glucose, body condition, packed cell volume, natural antibody agglutination, white blood cell counts and ratios and erythrocyte sedimentation rate to characterize the long-term effects of differential resource availability in these two snake populations 3 years after this major ecological disturbance. We collected blood samples at three time points from cottonmouths on Seahorse Key ( n = 6 individuals) and Snake Key ( n = 13 individuals) in fall 2018. In due consideration of the small sample size, our study shows evidence that 3 years after the shift in waterbird nesting Seahorse Key cottonmouths exhibit a dampened acute stress response and presumptive impaired innate immune functions relative to cottonmouths on Snake Key. These results highlight the context-dependent nature of biomarkers and implicate the significant decrease in food resources on Seahorse Key in altering hormonal stress responses and innate immune functions, possibly leading to unknown long-term downstream effects. This study assessed the response of a wild population of pit viper to ecological disturbance in situ with the aim to improve our understanding of how animals cope with such perturbations and improve our capacity to make informed decisions for conservation.